2020
DOI: 10.3390/medicina56090463
|View full text |Cite
|
Sign up to set email alerts
|

Different TERT Expression between Colorectal Adenoma and Serrated Polyp

Abstract: Background and Objectives: Telomere regulation have an association with colorectal cancer. Previous studies demonstrated its implication in colorectal carcinogenesis. This study aimed to identify the role of telomerase reverse transcriptase (TERT) in colorectal carcinogenesis and determine TERT expression and their associated genes in precancerous lesions. Materials and Methods: TERT expression in 93 colorectal precursor lesions was analyzed. This included 61 tubular adenomas (TAs) and 32 serrated polyps (SPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…4,8 Previous studies have shown that the telomerase activity plays an important role in the prognosis of CRC. 7 Both C228T and C250T mutations, identified in the TERT promoter region, cause the formation of a new binding site for E-twenty-six transcription factors and thereby increases the expression level of the TERT gene. 5,31 Hotspot mutations in the promoter region of the TERT gene were first identified in melanomas but were also frequently seen in various other tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,8 Previous studies have shown that the telomerase activity plays an important role in the prognosis of CRC. 7 Both C228T and C250T mutations, identified in the TERT promoter region, cause the formation of a new binding site for E-twenty-six transcription factors and thereby increases the expression level of the TERT gene. 5,31 Hotspot mutations in the promoter region of the TERT gene were first identified in melanomas but were also frequently seen in various other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…32 Besides, TERT promoter mutations were also not found in pheochromocytoma, gastrointestinal and kidney tumors, gastric cancer, colorectal precursor lesions, including tubular adenomas and serrated polyps. 7,33,34 On the other hand, Siraj et al reported TERT promoter mutations, -124C>T and -146C>T, in 13 different cancer types seen in Middle Eastern countries. They reported that TERT promoter mutations were most frequently detected in the 68.6% of bladder cancer, followed by 15.4% of thyroid cancer, 28.7% of nervous system tumors, 9.3% of prostate cancer, 3.7% of endometrial carcinoma, 1.4% of rhabdomyosarcoma, 1% of CRC, and 0.7% of breast cancer cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase reverse transcriptase (TERT), as the core component of telomerase regulation, is closely related to the development of cancer and cell growth [5]. Significantly elevated expression levels of human TERT (hTERT) have been found in most human malignancies, such as sarcomas [6], brain tumors [7], colorectal tumors [8], and breast cancer [9], increasing the risk of tumor recurrence. Studies have shown that mutations and methylation in the hTERT promoter region play a crucial role in the regulation of hTERT transcription levels and telomerase activity [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with serrated polyposis syndrome and their pedigree members are recommended to undergo regular colonoscopic surveillance and immediate removal of the polyps Level of evidence: III Grade of recommendation: B Approval rate: 97.5%Serrated polyposis syndrome is a genetic disease characterized by multiple serrated polyps in the colorectum 280. The World Health Organization (WHO) recommends serrated polyposis syndrome to be diagnosed when meeting any of the following criteria: (a) ≥5 serrated lesions/polyps proximal to the rectum, all are ≥5 mm in size, of which at least two polyps are ≥10 mm; (b) at least 20 serrated lesions/polyps in any size distributed throughout the large bowel, of which ≥5 polyps are proximal to the proximal rectum 281.…”
mentioning
confidence: 99%